A new species of the genus Brachytydeus Thor sensu André (Acari: Tydeidae) and a key to all known species from Peru - Escobar-Garcia, Hector Alonso [UNESP]; de Andrade, Daniel Júnior [UNESP]; Ueckermann, Edward A.; André, Henri M. (My University, 2023)
Brachytydeus juanjosei sp. nov., a new species of Neotropical Tydeidae, is illustrated and described from females, males, and a tritonymph collected from the leaves of a native forest tree, Neltuma piurensis (Fabaceae), from Department of Piura in north-western Peru. The new tydeid mite was found all year long, but more frequently observed during spring in high populations (September/December). A key to the known Peruvian species of the subfamily Tydeinae is provided.
Keywords: algarrobo; Prostigmata; Systematics; Taxonomy mites; Trombidiformes; Tydeoidea